The novel ciliogenesis regulator DYRK2 governs Hedgehog signaling during mouse embryogenesis - Yoshida, Saishu (eLife, 2020)
Mammalian Hedgehog (Hh) signaling plays key roles in embryogenesis and uniquely requires primary cilia. Functional analyses of several ciliogenesis-related genes led to the discovery of the developmental diseases known as ciliopathies. Hence, identification of mammalian factors that regulate ciliogenesis can provide insight into the molecular mechanisms of embryogenesis and ciliopathy. Here, we demonstrate that DYRK2 acts as a novel mammalian ciliogenesis-related protein kinase. Loss of Dyrk2 in mice causes suppression of Hh signaling and results in skeletal abnormalities during in vivo embryogenesis. Deletion of Dyrk2 induces abnormal ciliary morphology and trafficking of Hh pathway components. Mechanistically, transcriptome analyses demonstrate down-regulation of Aurka and other disassembly genes following Dyrk2 deletion. Taken together, the present study demonstrates for the first time that DYRK2 controls ciliogenesis and is necessary for Hh signaling during mammalian development.